Imaging the Human Prostate Gland Using 1-µm-Resolution Optical Coherence Tomography. - Gardecki, Joseph A.; Singh, Kanwarpal; Chin-Lee Wu; Tearney, Guillermo J. (Archives of Pathology & Laboratory Medicine, 2019)
Context.--The accuracy of needle biopsy for the detection of prostate cancer is limited by well-known sampling errors. Thus, there is an unmet need for a microscopic screening tool that can screen large regions of the prostate comprehensively for cancer. Previous prostate imaging by optical coherence tomography (OCT) has had insufficient resolution for imaging cellular features related to prostate cancer. We have recently developed microoptical coherence tomography (lOCT) that generates depth-resolved tissue images at a high frame rate with an isotropic resolution of 1 lm. Objective.--To demonstrate that optical images obtained with lOCT provide cellular-level contrast in prostate specimens that will enable differentiation and diagnosis of prostate pathologies. Design.--Fresh prostate specimens obtained from surgical resections were scanned with lOCT ex vivo. Histologic features in the lOCT images were correlated to the corresponding conventional histology. Results.--Findings indicate that lOCT is capable of resolving many of the architectural and cellular features associated with benign and neoplastic prostate. Conclusions.--Because lOCT can be implemented in a small-diameter flexible probe, this study suggests that highresolution lOCT imaging may be a useful tool for needlebased virtual biopsy of the prostate gland.